2014
DOI: 10.1167/14.7.12
|View full text |Cite
|
Sign up to set email alerts
|

Visual sensitivity is a stronger determinant of illusory processes than auditory cue parameters in the sound-induced flash illusion

Abstract: The sound-induced flash illusion (SIFI) is a multisensory perceptual phenomenon in which the number of brief visual stimuli perceived by an observer is influenced by the number of concurrently presented sounds. While the strength of this illusion has been shown to be modulated by the temporal congruence of the stimuli from each modality, there is conflicting evidence regarding its dependence upon their spatial congruence. We addressed this question by examining SIFIs under conditions in which the spatial relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 38 publications
9
25
0
Order By: Relevance
“…Our subjects generally weighted ILS higher than ITDs, which is consistent with a previous observation that the former may be more salient when binaural cues are presented over headphones in multisensory experiments (Kumpik et al, 2014). This is likely to be because our stimuli were bandpass filtered from 0.5-16 kHz, which would have removed some of the fine-structure ITD information from the HRTF and thus made the ITD less salient than might otherwise be expected (Wightman and Kistler, 1992).…”
Section: Discussionsupporting
confidence: 92%
“…Our subjects generally weighted ILS higher than ITDs, which is consistent with a previous observation that the former may be more salient when binaural cues are presented over headphones in multisensory experiments (Kumpik et al, 2014). This is likely to be because our stimuli were bandpass filtered from 0.5-16 kHz, which would have removed some of the fine-structure ITD information from the HRTF and thus made the ITD less salient than might otherwise be expected (Wightman and Kistler, 1992).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, some studies have shown that under certain conditions, inferences regarding the perceptual nature of the illusory flash can be made (McCormick and Mamassian, 2008). Such studies have suggested that a higher SiFI effect corresponds to a lower sensitivity; the lower perceptual sensitivity, calculated by d' , can be considered a measure of susceptibility to the illusion (McCormick and Mamassian, 2008;Kumpik et al, 2014). In the present study, the RS of auditory stimuli decreased the perceptual sensitivity of auditory stimuli, which resulting in lower auditory dominance.…”
Section: The Effects Of Repetition Suppression On Sifisupporting
confidence: 44%
“…A lower perceptual sensitivity could be the cause of a higher SiFI and could therefore be a measure of susceptibility to the illusions (McCormick and Mamassian, 2008;Kumpik et al, 2014). This, together with the RS, could influence the intensity of neural activity in the perceptual sensitivity to the stimuli (Grill-Spector and Malach, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SIFI is an illusion in which brief visual and auditory stimuli are presented rapidly, and the number of auditory stimuli influences the reported number of visual stimuli. Signal-detection theory analysis has demonstrated that illusory flashes are accompanied by measured changes in sensitivity (and not only bias) 26 , 27 , suggesting that this illusion is due in part to a change in perception. However, illusory flashes are not perceived in the same way as real flashes: when offered a third ‘not-one, not-two’ option many subjects choose it [28] .…”
Section: Section I Behavioral Assaysmentioning
confidence: 99%